Studi Penerapan Manajemen Konstruksi Pada Proyek Pembangunan Jalan Akses Tol Makassar New Port - Pratiwi, Suciati; Abduh, M. Natsir; Yunus, Ahmad Yauri (Program Studi Teknik Sipil Universitas Bosowa, 2026)
Construction management encompasses managing the planning, organizing, implementing, and supervising phases of a project to achieve optimal results in terms of time, cost, and quality. In the Makassar New Port Toll Access Road construction project, several challenges were identified, including mismatches between rebar connections and working drawings, delays in material deliveries, and concrete slump values that did not meet specifications. This study aims to determine the variables influencing the effective implementation of construction management in this project. Data were gathered using questionnaires distributed to 36 respondents and analyzed for validity and reliability with the Statistical Product and Service Solution program. The Relative Importance Index method was utilized to assess the impact of each variable. The findings revealed that supervision was the most influential variable, achieving the highest Relative Importance Index value of 0.97. This underscores the critical role of supervision in managing project activities, preventing deviations, and reducing the risk of construction failures